2005
DOI: 10.1080/10903120590924843
|View full text |Cite
|
Sign up to set email alerts
|

Use of Treat-and-Release Medical Directives for Paramedics at a Mass Gathering

Abstract: Treat-and-release medical directives for paramedics at mass gatherings may help divert patients from requiring care at a medical facility. Future research is needed to determine the safety (morbidity and mortality) of these directives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Maintaining the level of service during the event involves accessibility to off-venue destinations, awareness of increased workload caused by mass gatherings outside of the area, and the deployment of operative resources in the venue. According to previous studies, mass gatherings mainly increase workload for the EMS, healthcare facilities, and police forces [5,6,8,[10][11][12][14][15][16]20,21,[25][26][27][28][29]31,[48][49][50][51]. This supports the findings of the present study, as the informants pointed out that operative workload during the event builds for EMS and police, whereas the increase in workload for rescue service operative personnel is only minor.…”
Section: Actions During the Eventsupporting
confidence: 90%
See 2 more Smart Citations
“…Maintaining the level of service during the event involves accessibility to off-venue destinations, awareness of increased workload caused by mass gatherings outside of the area, and the deployment of operative resources in the venue. According to previous studies, mass gatherings mainly increase workload for the EMS, healthcare facilities, and police forces [5,6,8,[10][11][12][14][15][16]20,21,[25][26][27][28][29]31,[48][49][50][51]. This supports the findings of the present study, as the informants pointed out that operative workload during the event builds for EMS and police, whereas the increase in workload for rescue service operative personnel is only minor.…”
Section: Actions During the Eventsupporting
confidence: 90%
“…According to our results, multi-authority collaboration in the pre-event planning phase manifests, for example, as consultation of an EMS specialist regarding the planned attendee numbers, and the competence of the on-site medical care provided in the emergency plan. Previous studies showed that having medical professionals available among the first-aid providers and the use of treat-and-release directives have an impact on the need for transport to hospital, and in turn affect the workload for the EMS system and healthcare facilities [15,16,18,21,23]. According to an Australian study by Zeitz et al [8], the increase in workload for the rescue service in mass gatherings with a total of 5.7 million attendees in a two-year period, was only minor.…”
Section: Co-operation In the Pre-planning Phasementioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] This review did not include any medical records or review of personal health information. The research period was started in 2003 because the publication date of the last review on interventions during mass gatherings was the previous year; however, the scope of the review was more narrow as only articles that reported data on noncommunicable health issues were only included.…”
Section: Review Designmentioning
confidence: 99%
“…To consider a T&R system, it is necessary that on-scene paramedics be able to appropriately triage patients into suitable care pathways (emergency, primary or self-care) according to their need for treatment and transport. Paramedics have previously used treat-and-release medical directives successfully at mass gathering events 4. It has also been demonstrated that emergency care practitioners (ECP; paramedics and nurses with an extended skill-set operating as autonomous practitioners) can have clear benefits to patients within certain emergency healthcare settings 5.…”
Section: Introductionmentioning
confidence: 99%